2021
DOI: 10.1111/bph.15543
|View full text |Cite
|
Sign up to set email alerts
|

THE CONCISE GUIDE TO PHARMACOLOGY 2021/22: Transporters

Abstract: The Concise Guide to PHARMACOLOGY 2021/22 is the fifth in this series of biennial publications. The Concise Guide provides concise overviews, mostly in tabular format, of the key properties of nearly 1900 human drug targets with an emphasis on selective pharmacology (where available), plus links to the open access knowledgebase source of drug targets and their ligands (https://www.guidetopharmacology.org), which provides more detailed views of target and ligand properties. Although the Concise Guide constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
154
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 177 publications
0
154
0
Order By: Relevance
“…Key protein targets and ligands in this article are hyperlinked to corresponding entries in http://www.guidetopharmacology.org , the common portal for data from the IUPHAR/BPS Guide to PHARMACOLOGY, 46 and are permanently archived in the Concise Guide to PHARMACOLOGY 2021/22. 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…Key protein targets and ligands in this article are hyperlinked to corresponding entries in http://www.guidetopharmacology.org , the common portal for data from the IUPHAR/BPS Guide to PHARMACOLOGY, 46 and are permanently archived in the Concise Guide to PHARMACOLOGY 2021/22. 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…Key protein targets and ligands in this article are hyperlinked to corresponding entries in the IUPHAR/BPS Guide to PHARMACOLOGY (http://www.guidetopharmacology.org/) and are permanently archived in the Concise Guide to PHARMACOLOGY 2021/22 (Alexander, Christopoulos, et al, 2021; Alexander, Fabbro, et al, 2021; Alexander, Kelly, et al, 2021a, b; Alexander, Mathie, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies 41,42 have shown that tramadol is associated with an increased risk of mortality in the adult population compared to NSAIDs or non‐use. However, both study results were limited by confounding by indication as patients with multiple comorbidities such as cardiovascular, renal or bleeding disorders, who were at higher risk of mortality, may have been prescribed tramadol due to potential contraindication to NSAIDs.…”
Section: Discussionmentioning
confidence: 99%